2010
DOI: 10.1093/molehr/gaq099
|View full text |Cite
|
Sign up to set email alerts
|

SPAG4L/SPAG4L-2 are testis-specific SUN domain proteins restricted to the apical nuclear envelope of round spermatids facing the acrosome

Abstract: SUN domain proteins are integral proteins of the inner nuclear membrane and functions in linkage of the nuclear lamina to the cytoskeleton. Moreover, SUN domain proteins seem to mediate the tethering of the centrosome to the nuclear membrane, and they are involved in telomere attachment to the nuclear envelope in meiotic cells, and in germ cell development in invertebrates. In contrast to the widely expressed SUN domain proteins in mammals, SUN1 and SUN2, which have been analysed in great detail, there is virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 57 publications
1
59
2
Order By: Relevance
“…In this work, we have characterized a new family of proteins located in the INM, the absence of which leads to the disruption of the bridging structure required for acrosome attachment on the nucleus. Interestingly, Sun5, recently described in the NE facing the acrosome in mouse, shows a spatiotemporal pattern of expression very similar to that of Dpy19l2 (Frohnert et al, 2011). Our results show that SUN5 and DPY19L2 clustered in the NE in transfected HEK cells and partially colocalized.…”
Section: Dpy19l As a Functional Partner Of Linc Complexsupporting
confidence: 74%
See 1 more Smart Citation
“…In this work, we have characterized a new family of proteins located in the INM, the absence of which leads to the disruption of the bridging structure required for acrosome attachment on the nucleus. Interestingly, Sun5, recently described in the NE facing the acrosome in mouse, shows a spatiotemporal pattern of expression very similar to that of Dpy19l2 (Frohnert et al, 2011). Our results show that SUN5 and DPY19L2 clustered in the NE in transfected HEK cells and partially colocalized.…”
Section: Dpy19l As a Functional Partner Of Linc Complexsupporting
confidence: 74%
“…DPY19L2 was tagged with GFP, and DPY19L3 and SUN5 were tagged with DDK. We chose SUN5 as a marker of the inner nuclear membrane (INM) because it was recently demonstrated that SUN5 is positioned in round spermatids in the NE facing the acrosomal vesicle (Frohnert et al, 2011).…”
Section: Dpy19l2 Is a Protein Of The Inner Nuclear Membranementioning
confidence: 99%
“…In this context consideration should be given to a novel testis-specific SUN domain protein (SPAG4L-2), a transmembrane protein restricted to the apical nuclear region of round spermatids that faces the AV, as a possible component of a protein linkage complex that anchors the AV to the nuclear membrane [67]. It is well documented that SUN and KASH domain proteins, spanning the nuclear envelope, organize a diversity of nucleo-cytoplasmic connections, including tethering microtubules and centromeres to the nuclear envelope [68].…”
Section: Discussionmentioning
confidence: 99%
“…Male germ-line cells contain three other SUN proteins (Kracklauer et al, 2013), SUN3 (Göb et al, 2010), SUN4 (originally termed Spag4 (Shao et al, 1999;Tarnasky et al, 1998)) and SUN5 (also known as Spag4-like (Frohnert et al, 2011;Jiang et al, 2011)). Each of these conforms to the same general domain organization as SUN1/2 (Hasan et al, 2006;Liu et al, 2007).…”
Section: Mammalian Somatic Cells Contain Two Partially Redundant Sun mentioning
confidence: 99%